2017
DOI: 10.17814/mechanik.2017.1.15
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical properties of AlSi coatings made by PVD technology

Abstract: The mechanical properties (microhardness and scratch test) of AlSi coatings made by PVD magnetron sputtering method from alloys with 7-20%Si were compared. Higher concentration of Si increased deformation resistance of the coating, expressed by depth of scratch. Improved mechanical properties had coatings from alloys modified by TiBAl refiner. KEYWORDS: protective coatings, PVD coatings, AlSi alloys Porównano mechaniczne właściwości (mikrotwardość i test rysy) powłok AlSi wykonanych metodą PVD magnetronowego r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…A similar branched structure of the Si grains within the Al matrix is found in literature for Al-20Si sputtered coatings as well [50,51]. In the literature, no heating was mentioned so it is suggested that the sputtering took place at room temperature.…”
Section: Fig 8: Sem Micrographs Of the Isothermal Oxidized Samples (8...supporting
confidence: 78%
“…A similar branched structure of the Si grains within the Al matrix is found in literature for Al-20Si sputtered coatings as well [50,51]. In the literature, no heating was mentioned so it is suggested that the sputtering took place at room temperature.…”
Section: Fig 8: Sem Micrographs Of the Isothermal Oxidized Samples (8...supporting
confidence: 78%